VAT's going onn ; Great minds think alike ; Volleyball fun in Boracay [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
levy. The second part takes a look at existing patent laws and their implementation. The last part is about beach volleyball and its difference from indoor volleyball.
The first part is about the expanded value added tax abolishing other taxes on goods and services but imposes a flat 10
VAT's going on! (15 min.) -- Great minds think alike (15 min.) -- Volleyball fun in Boracay (15 min.)
VHS.
Reporters, Marga Ortigas, Luchi Cruz-Valdes.
Keywords: Value-added tax -- Philippines; Beach volleyball -- Philippines -- Boracay; Patent law and legislation -- Philippines